Jihad Sufi - Muhammad Amin Sahib (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2020)
This paper explores what the meaning of jihad and Sufi is and how a Sufi jihad. The aim of this research is to correct the wrong understanding of Sufism and Sufi teachings and explain that Sufism in Sufism never lags in jihad with its various aspects. Jihad is all forms of maximum effort for the application of Islamic teachings and eradication of tyranny, both for oneself, society and the universe by not knowing despair, surrender, and strings attached, both through physical struggle, emotions, possessions, energy, and science in order reach the pleasure of Allah Almighty. Being Sufi is a person who tries to purify and decorate himself with commendable qualities to draw closer to Allah. Sufis not only adorn themselves with praiseworthy qualities and mahdhah worship rites only to God Almighty, but a Sufi person is still required to draw closer to Allah swt with jihad efforts such as spiritual jihad, ethical jihad, intellectual jihad and politics. Keyword: Islam; Jihad; Sufi